Pengaruh Kompetensi Profesional Guru PAK terhadap Motivasi Belajar Siswa Kelas VIII di SMP Negeri 2 Siborongborong Tahun Pembelajaran 2024/2025 - Rosverawati Batubara; Sudirman Lase; Maria Widiastuti; Hasudungan Simatupang; Rusmauli Simbolon (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The purpose of this study was to determine the positive and significant influence of the professional competence of PAK teachers on the learning motivation of class VIII students at SMP Negeri 2 Siborongborong 2024/2025. The method used in this study is the quantitative inferential statistical method. The population is all Christian students of class VIII SMP Negeri 2 Siborongborong 2024/2025 totaling 254 people and a sample of 48 people is determined, which is 20% of the population using random sampling techniques. Data were collected using a positive closed questionnaire of 35 items, namely 15 items for variable X and 20 items for variable Y. The results of the data analysis showed that there was a positive and significant influence of the professional competence of PAK teachers on the learning motivation of class VIII students at SMP Negeri 2 Siborongborong 2024/2025 as evidenced by the following data analysis: 1) a positive relationship test obtained a value of rxy = 0.618> rtable ( = 0.05, n = 48) = 0.284 thus it is known that there is a positive relationship between variable X and variable Y. 2) A significant relationship test obtained a value of tcount = 5.330> ttable ( = 0.05, dk = n-2 = 46) = 2.021 thus there is a significant influence between variable X and variable Y. 2) Influence test: a) Regression equation test, the regression equation Y ̂=